Choroby i ich objawy w XIX-wiecznym Słowniku polsko-łacińsko-łotewskim Jana Kurmina - Szamryk , Konrad Kazimierz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
This article presents an analysis of the names of diseases and their symptoms in Słownik polsko-łacińsko-łotewski (The Polish-Latin-Latvian dictionary) by Jan Kurmin (ed. Vilnius, 1858). The number of excerpted lexical items (377) is presented in 11 semantic fields (from the most expanded to the smallest one): diseases of the motor system, skin diseases, respiratory system diseases, symptoms of multiple diseases, internal diseases, infectious diseases, diseases of the sensory organs, wounds and cuts, digestive system diseases, mental diseases, cardiovascular diseases. The analysis shows that despite the high ability to observe symptoms, the knowledge of treatments remained limited, which is why the dictionary presents mostly diseases that can be easily observed with the unaided eye. The non-professional character of the dictionary is also evidenced by the use of synonymous sequences, vocabulary with indistinct meaning, and descriptive names of diseases.